If it's not what You are looking for type in the equation solver your own equation and let us solve it.
72=6(a+2)
We move all terms to the left:
72-(6(a+2))=0
We calculate terms in parentheses: -(6(a+2)), so:We get rid of parentheses
6(a+2)
We multiply parentheses
6a+12
Back to the equation:
-(6a+12)
-6a-12+72=0
We add all the numbers together, and all the variables
-6a+60=0
We move all terms containing a to the left, all other terms to the right
-6a=-60
a=-60/-6
a=+10
| 12x-20=-84 | | 0.10m+24.95=0.20+19.95 | | 9=-3(2n-7) | | Y=5x-125 | | 7^2x-3=93 | | s/10=4 | | 3.953+8.95b=47.65, | | Y=125x-5 | | v/10=3 | | c-19c=-18c | | 5(c+40)=400 | | Y=125x+5 | | d5=−3 | | 5+y+y=57 | | 3/4b−2≤2b+8;b=−4 | | -84=-4(1+5x) | | 10=v/9 | | 4(x+3)=4x+12* | | 70t+35=245 | | 4.2x+6=3x=12 | | -9(5+8d)d=6 | | -1.7-1.6c=-0.42 | | 6x-10=124 | | 7x+21=59.5 | | 3=2t=t | | -4x-19=19-5x | | (2x+10)(2x+20)=216 | | 6t-6=-6t-18 | | f5−20=−24 | | 9.75h+1.00=40 | | -3y+2=-1 | | x/2+3=0.5 |